P27 Preventing unnecessary CT coronary angiography by utilising previous CT thoracic imaging: a retrospective analysis. (21st September 2022) - Fatima, Rida; Khan, Sanaullah; Azhar, Amber; Anosike, Chinedum; Farag, Ahmed
Abstract : Objective: CT coronary angiography (CTCA) is an effective first-line investigation in patients presenting with stable chest pain, with low-intermediate predicted risk of coronary artery disease. However, it is much less effective in patients with extensive coronary artery disease, due to calcification reducing image quality. Our objective was to analyse whether unnecessary CTCA's could have been avoided if previous CT imaging were reviewed to assess for severe coronary artery calcification (CAC). Methods: Patients who underwent a cardiac CT and who were found to have high CAC scores were identified between January 2021 to June 2022. Total of 234 patients were identified. Data was retrospectively analysed using PACS and CRIS for radiology images/reports, and Lorenzo for patient notes. Results: 79 (34%) patients had previous CT imaging. 56 of these 79 patients (71%) demonstrated significant CAC detectable on old CT images and hence angiography was not done. Conclusion: A significant proportion of patients who underwent a CTCA with high CAC scores had previous CT imaging which demonstrated severe CAC. Reviewing previous CT imaging reduces delays in patient management, pressures in the CT department, overall NHS costs, patient travel (thereby reducing costs and environmental impact) and patient radiation.